Physical Interior Setting of Angkringan Vendor on Jalan Tukad Barito Denpasar - Persada, Nyoman Gema Endra; Rahayu, Ni Nyoman Sri (Pendhapa, 2023)
The angkringan business is spreading rapidly in big cities throughout Indonesia with a strong characteristic with a Javanese atmosphere, cheap food and an intimate atmosphere. Another characteristic of angkringan is the mobility and territoriality of the traders, which is not very visible in angkringan on Jalan Tukad Barito Denpasar. An angkringan that uses a shop parking area that is closed at night is studied based on interior design components such as floors, walls and ceilings. Qualitative descriptive research method with observation of phenomena that occur accompanied by interviews and photo documentation. Observations were mapped using a place centered map which were grouped based on existing functions in the form of food counters, kitchens, dining areas for visitors and live music areas. Other findings are the cart design which still maintained, the goods storage system, the phenomenon of full shop rentals and the importance of live music in angkringan.